DISPUTES CAUSED BY INCOMPATIBILITY WITH THE LAND REGISTRATION PROCESS - Randy Tulus Jordi Marpaung; Mella Ismelina Farma Rahayu (Warmadewa Press, 2024)
Land registration is a process step in order to obtain legal land ownership status. In the process, land buying and selling needs to be done before a Land Deed Officials so that land registration can be carried out. The National Land Agency as the land registration center carries out the land registration process systematically. The form of land registration is the issuance of a land certificate, but not necessarily the issuance of a land certificate can explain that the land has a strong legal basis because in practice there are still problems with court land disputes. The purpose of this research is to find out the High Court Decision Number 323/PDT/2015/PT.BDG when viewed from the aspect of National Land Law and legal certainty for parties who hold proof of ownership of land rights (certificate) as well as the accountability of government institutions that issue land certificates that turn out to be problematic. The research method uses a normative legal approach with qualitative descriptive data analysis. The results of the study explain that although the system method used by the National Land Agency for land registration is in accordance with Government Regulation Number 24 of 1997 concerning Land Registration, however, the physical data and documents that are required for land registration are still not in accordance so that the land certificate which should be the basis for land ownership turns out to cause conflict in the field because the area of the land does not match the area of the adjoining land.